ANALISIS PENGARUH KUALITAS PELAYANAN DAN EMOSI PASIEN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM PUSAT DR. SOERADJI TIRTONEGORO KLATEN (Riset Manajemen & Akuntansi, 2011)
The purpose of the research is to develop and examine an empirical model, the main factor that influences the patient satisfaction and describes the relation among service, quality, the patient emotion, hope, involvement and the patient behaviour intention. Data had been collected used a questionnaire was given to 200 respondens at random during Mei 2011. From the result of questionnaire distribution, they got back 197 questionnaire and there were 193 questionnaite that can be applied due to 4 questionnaire which were not filled completely. Analysis this data using Structural Equation Model (SEM). The research result is known that patient feels satisfied with the service quality given by the hospital. Because of that, the patient satisfaction will increase if service quality also increases